2014
DOI: 10.3354/ab00569
|View full text |Cite
|
Sign up to set email alerts
|

Selective settlement by larvae of Membranipora membranacea and Electra pilosa (Ectoprocta) along kelp blades in Nova Scotia, Canada

Abstract: Many larval sessile marine invertebrates exhibit settlement preferences, and larval behavioral responses to cues at settlement can ultimately influence the distribution of adults and an individual's lifetime fitness. Two epifaunal bryozoans, the invasive Membranipora membranacea and the native Electra pilosa, commonly co-occur on kelp species in the subtidal habitats of Nova Scotia, Canada. Outbreaks of M. membranacea have been linked to mass defoliation of the kelp canopy; however, E. pilosa has not been asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Warm temperatures also increase settlement and growth of the invasive bryozoan Membranipora membranacea, which encrusts, weakens, and causes fragmentation of kelp blades (Saunders & Metaxas 2009, Scheibling & Gagnon 2009). Furthermore, M. membranacea has a settlement affinity to new tissue adjacent to the basal meristem (Brumbaugh et al 1994, Denley et al 2014, which may increase the likelihood of erosion of the meristem as the colony grows towards the stipe (Ryland & Stebbing 1971). The combined effects of increasing temperatures late in the summer and encrustation by M. membranacea, coupled with increased wave activity in the autumn, likely caused the considerable loss of blade tissue of the large rockattached kelps, such that only bare stipes remained.…”
Section: Dislodgement and Survival Of Kelpmentioning
confidence: 99%
“…Warm temperatures also increase settlement and growth of the invasive bryozoan Membranipora membranacea, which encrusts, weakens, and causes fragmentation of kelp blades (Saunders & Metaxas 2009, Scheibling & Gagnon 2009). Furthermore, M. membranacea has a settlement affinity to new tissue adjacent to the basal meristem (Brumbaugh et al 1994, Denley et al 2014, which may increase the likelihood of erosion of the meristem as the colony grows towards the stipe (Ryland & Stebbing 1971). The combined effects of increasing temperatures late in the summer and encrustation by M. membranacea, coupled with increased wave activity in the autumn, likely caused the considerable loss of blade tissue of the large rockattached kelps, such that only bare stipes remained.…”
Section: Dislodgement and Survival Of Kelpmentioning
confidence: 99%
“…Even though bryozoans do not seem to benefit from algae in terms of growth, other factors have been suggested that support preferred settlement on algae. Those include low competition for space (Manríquez and Cancino 1996), minimized risk of predation and thus, increased longevity of colony survival (Nikulina and Schäfer 2006; Denley et al 2014), lower risk of smothering by sediment (Denley et al 2014), supply of organic matter (food) by macroalgae (Manríquez and Cancino 1996), and higher food availability as the algae sways through the water column (Okamura 1988; Pratt 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller colonies of M. membranacea were able to avoid whole‐colony mortality, presumably as a result of selective settlement toward younger more basal regions on blades of host kelps (Denley et al. ). Selective settlement allows M. membranacea recruits the maximum amount of time to grow before becoming at risk of mortality due to breakage or erosion of the kelp substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, its population dynamics have been well studied, both in Nova Scotia and circumglobally (see Saunders and Metaxas , , , Denley et al. ). Unlike most corals (e.g., Pisapia and Pratchett ), the sheet‐like growth of M. membranacea makes it possible to visually measure partial mortality as a reduction in two‐dimensional colony surface area, allowing the full extent of partial mortality to be quantified from a single photograph.…”
Section: Introductionmentioning
confidence: 99%